Identifikasi Hubungan Iklim Mikro pada Tanaman Kopi Robusta (Coffea chanepora) Dataran Rendah - Widiyani, Dimas Prakoswo; Gusta, Adryade Reshi; Aziz, Abdul; Usodri, Kresna Shifa; Hartono, Joko S. S; Hamdani, Hamdani (Kadiri University - Faculty of Agriculture, 2022)
The provinces of West Lampung and Tangamus are areas of robusta coffee development and as one of the leading Indonesian coffee producers in Indonesia. Lampung Province has a geographical area and climate suitable for the growth and development of robusta coffee. Robusta coffee, although derived from vegetative plants, often shows varied phenotypic responses based on environmental differences. A plant must be affected by internal factors such as genetics or from outside such as the environment, the process of growth and development. Coffee plants tend to want to grow in the highlands so that in the lowlands they don't. The research is aimed at identifying microclimate conditions in lowland coffee plantations, as a reference in environmental modification in order to optimize growth and produce optimal productivity. Early research was carried out in August – November 2021 in the experimental garden of the Lampung State Polytechnic. The method in this experiment uses a survey method. The results obtained are microclimate conditions that vary between plots and there is a unidirectional correlation between climate elements and in line with production results based on linear regression tests carried out, namely with a value > 0.5 which indicates that each component of the climate element is very strong in influencing one with the other. others as well as production. Provinsi Lampung Barat dan Tangamus merupakan daerah pengembangan kopi robusta dan sebagai salah satu produsen kopi Indonesia ternama di Indonesia. Provinsi Lampung memiliki wilayah geografis dan iklim yang sesuai untuk pertumbuhan dan perkembangan kopi robusta. Kopi robusta, meskipun berasal dari tanaman vegetatif, sering menunjukkan respon fenotipik variatif berdasarkan perbedaan lingkungannya. Suatu tanaman pasti terpengaruh faktor dari dalam seperti genetis atau dari luar seperti lingkungan, proses pertumbuhan dan perkembangannya. Tanaman kopi cenderung menghendaki tumbuh pada dataran tinggi sehingga pada dataran rendah tidak. Adapun penelitian ditujukan mengidentifikasi kondisi iklim mikro di perkebunan kopi dataran rendah, sebagai acuan dalam modifikasi lingkungan guna mengoptimalkan pertumbuhan serta menghasilkan produktivitas yang optimal. Penelitian dini dilaksanakan pada Agustus – November 2021 dikebun pecobaan Politeknik Negeri Lampung. Metode dalam percobaan ini menggunakan metode survei. Hasil yang diperoleh terdapat kondisi iklim mikro yang bervariatif antar plot serta terdapat korelasi yang searah antar unsur iklim serta selaras dengan hasil produksi berdasarkan uji regresi linier yang dilakukan, yaitu dengan nilai > 0,5 yang mengindikasikan setiap komponen unsur iklim sangat kuat dalam mempengaruhi satu dengan yang lainya begitupun juga dengan produksi.